HYPERTENSIVE DISORDERS IN PREGNANCY AND PRETERM DELIVERY: A CASE CONTROL STUDY - Kjaev, Ivo; Joksimovic, Marija; Milkovski, Daniel; Naumovska, Rosa; Nivichka, Jana; Anastasova, Sasha; Nikolovska, Elena; Simeonova, Sladjana; Aleksioska, Irena; Koteva, Maja (Journal of Morphological Sciences; Vol 7 No 3 (2024): JMS, 2024)
Introduction. Hypertensive disorders in pregnancy, including gestational hypertension and preeclampsia, are major contributors to global rates of preterm birth. Both conditions pose significant risks to maternal and neonatal health, potentially leading to neonatal morbidity, mortality, and long-term complications for mothers. Objective. This study aimed to evaluate the relationship between hypertensive disorders in pregnancy and the incidence of preterm delivery. Specifically, it compared preterm birth rates between women with gestational hypertension or preeclampsia and a control group of normotensive pregnant women. Materials and Methods. This case-control study included 81 pregnant women attending the Clinic for Gynecology and Obstetrics. Participants were enrolled between the 28th and 36th week of gestation and categorized into two groups: 1) 51 women diagnosed with gestational hypertension or preeclampsia, and 2) 30 normotensive women. The primary outcome, gestational age at delivery, was compared between the groups. Statistical analyses were conducted using the Student's t-test and Chi-square test to determine significant differences. Results. A statistically significant difference in preterm delivery rates was found between the groups (p < 0.001). Of the 25 preterm deliveries in the study group (49%), the majority (72%) occurred between 34-36 weeks of gestation. In contrast, only 2 (6%) of the control group experienced preterm birth, both at 32 weeks of gestation. Conclusion: Hypertensive disorders in pregnancy significantly increase the risk of preterm birth, with the majority of cases occurring in the late preterm period. These findings highlight the importance of careful monitoring and management of hypertensive pregnancies to reduce preterm birth risks. Keywords:  hypertension, pregnancy, premature, delivery.